MORFOLOGI DAN TRUSS MORFOMETRIK Scylla serrata DAN Scylla tranquebarica ASAL PULAU BANGKA - Berliani, Sonia; Bidayani, Endang; Kurniawan, Ardiansyah (Program Studi Akuakultur, Universitas Bangka Belitung, 2024)
Managing Mud Crab resources is the main thing that must be done to maintain the sustainability of these resources so that they can continue to make an economic contribution to society. A study of Mud Crabs that can be carried out is on morphometric trusses and their morphology. This research was carried out from April to June 2022 with sampling locations in mangroves in Pagarawan Village, Bangka Regency, and Kurau Village, Central Bangka Regency. The Mangrove Crab species found at sampling locations in Bangka and Central Bangka were Scylla serrata and Scylla tranquebarica. There are morphological variations in crab carapace color between sampling locations. The morphometrics of mud crabs from Bangka were larger but showed no significant differences. Differences in substrate type and environmental conditions are predicted to influence the emergence of variations. The location of the sampling locations, which are still connected to the same sea waters, allows the crabs to have close genetic and population relationships, making the variation insignificant.